1985
DOI: 10.1073/pnas.82.10.3320
|View full text |Cite
|
Sign up to set email alerts
|

Developmentally regulated expression of the bean β-phaseolin gene in tobacco seed

Abstract: Recombinant phage X177.4 contains a gene for j3 phaseolin, a major storage glycoprotein of French bean seed. A 3.8-kilobase Bgl II-Bam}Il fragment containing the entire 1700-base-pair coding region, together with 863 base pairs of 5' and 1226 base pairs of 3' flanking sequence, was inserted into the A66 Ti plasmid of Agrobacterium tumefaciens and used to transform tobacco. The level of phaseolin in the seeds of plants regenerated from cloned tissue was 1000-fold higher than in other tissues. The molecular weig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
116
2
2

Year Published

1985
1985
2014
2014

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 220 publications
(133 citation statements)
references
References 27 publications
13
116
2
2
Order By: Relevance
“…3B). As reported earlier (Sengupta-Gopalan et al, 1985), in addition to the authentic-size /3-phaseolin protein, the seeds also showed the accumulation of small molecular mass immunoreactive products, probably representing specific cleavage products. Whereas the leaf and stem showed very low levels of small molecular mass immunoreactive bands, the roots showed accumulation of a major immunoreactive band of 29 kD (Fig.…”
Section: Steady-state Accumulation Pattern Of the 15-kd Zein And J8-psupporting
confidence: 82%
“…3B). As reported earlier (Sengupta-Gopalan et al, 1985), in addition to the authentic-size /3-phaseolin protein, the seeds also showed the accumulation of small molecular mass immunoreactive products, probably representing specific cleavage products. Whereas the leaf and stem showed very low levels of small molecular mass immunoreactive bands, the roots showed accumulation of a major immunoreactive band of 29 kD (Fig.…”
Section: Steady-state Accumulation Pattern Of the 15-kd Zein And J8-psupporting
confidence: 82%
“…DHPS activity in the homozygous transgenic plant AE26 was also first detected at 14 days after anthesis but continued to rise dramatically until maturity ( Fig. 2A), as expected from its regulation by the phaseolin promoter (17). Free lysine accumulation in seeds of the control plants correlated with the activity of DHPS, reaching a maximum at 18-22 days after anthesis and then declining to its lowest level in mature seeds (Fig.…”
Section: Methodssupporting
confidence: 60%
“…In transgenic tobacco seeds analyzed as bulk samples, phaseolin protein (Sengupta-Gopalan et al, 1985) and P-phaseolin promoter-expressed mRNA (Riggs et al, 1989) or marker gene activity (Bustos et al, 1989) were first detected at a midmaturation stage, Deletion analysis of this promoter in transgenic tobacco revealed a complex set of regulatory regions within the sequence between +20 and -795 (Bustos et al, 1991). Since our promoter fragment extends only to -410, it retains only a subset of these domains.…”
Section: Discussionmentioning
confidence: 88%